2021
DOI: 10.1172/jci.insight.144068
|View full text |Cite
|
Sign up to set email alerts
|

In vivo grafting of large engineered heart tissue patches for cardiac repair

Abstract: Calcium transients. GCaMP6f EHTs were analyzed using standard methods (see Supplemental Methods), and parameters were calculated in pClamp. GCaMP6f cells were obtained courtesy of the Conklin laboratory (Gladstone Institutes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Even though no arrhythmic effects were observed, a sufficient electrical coupling was not obtained in these early approaches. 91 In a proof-of-concept study, engineered cardiac microtissue was utilized for transmural heart wall replacement. Transmural defects were generated using an aortic punch that resulted in a 6 mm diameter injury.…”
Section: Engineered Cardiac Microtissuementioning
confidence: 99%
See 1 more Smart Citation
“…Even though no arrhythmic effects were observed, a sufficient electrical coupling was not obtained in these early approaches. 91 In a proof-of-concept study, engineered cardiac microtissue was utilized for transmural heart wall replacement. Transmural defects were generated using an aortic punch that resulted in a 6 mm diameter injury.…”
Section: Engineered Cardiac Microtissuementioning
confidence: 99%
“…Here, the cardiac patch engrafted into the host myocardium and led to improved left ventricular function. Even though no arrhythmic effects were observed, a sufficient electrical coupling was not obtained in these early approaches 91 . In a proof‐of‐concept study, engineered cardiac microtissue was utilized for transmural heart wall replacement.…”
Section: Engineered Cardiac Microtissuementioning
confidence: 99%
“…The safety concern of cardiac patch therapy was limited to arrhythmias, which were generally transient and non-fatal [129][130][131]. It is noteworthy that a recently published study has revealed the efficacy of upscaled engineered heart tissue to improve left ventricular function and reduce the infarct size in the context of ischemic myocardial disease without documenting a significant difference in arrhythmogenicity, compared to a cell-free patch group in a rabbit model [132].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…With the vasculature or chambers inside, natural cardiac tissue is a hierarchically aligned structure with conductivity and strength, which is responsible to propagate and respond to electrical impulses by synchronized contractions that produce forces to pump blood. It challenges cardiac tissue engineering to construct engineered scaffolds with appropriate conductivity and stiffness to maintain physiological and contractile loads of the heart …”
Section: Introductionmentioning
confidence: 99%